Direct and Indirect Costs of Asthma Management in Greece: An Expert Panel Approach - Souliotis, Kyriakos; Kousoulakou, Hara; Hillas, Georgios; Bakakos, Petros; Toumbis, Michalis; Loukides, Stelios; Vassilakopoulos, Theodoros (Frontiers in Public Health, 2017)
Objective Asthma is a major cause of morbidity and mortality and is associated with significant economic burden worldwide. The objective of the present study was to map current resource use associated with the disease management and estimate the annual direct and indirect costs per adult patient with asthma. Methods A Delphi panel with 7 leading pulmonologists was conducted. A semi-structured questionnaire was developed to elicit data on resource use and treatment patterns. Unit costs from official, published sources were subsequently assigned to resource use to estimate direct medical costs. Indirect costs were estimated as number of work loss days. Cost base year was 2015, and the perspective adopted was that of the National Organization of Health Care Services Provision, as well as the societal. Results Patients with asthma are mainly managed by pulmonologists (71.4%) and secondarily by general practitioners and internists (28.6%). The annual cost of managing exacerbations was estimated at €273.1, while maintenance costs were estimated at €1,100.2 per year. Total costs of managing asthma per patient per year were estimated at €2,282, 64.4% of which represented direct medical costs. Of the direct costs, pharmaceutical treatment was the key driver, accounting for 63.9% and 41.2% of direct and total costs, respectively. Direct non-medical costs (patient travel and waiting time) were estimated at €152.3. Indirect costs accounted for 29% of total costs. Conclusion Asthma is a chronic condition, the management of which constrains the already limited Greek health care resources. . The increasing prevalence of the disease raises concerns as it could translate per patient costs into a significant burden for the Greek health care system. Thus, the prevention, self-management, and improved quality of care for asthma should find a place in the health policy agenda in Greece.